Dynamic Use of RSSI in LoRa Networks for Decision Making in Outdoor Applications - Carlos Munoz; Cristian Pesce; Ignacio Huircan; Oscar Villagra; Rodrigo Villalobos; Javier Riedemann (IEEE Access)
Livestock monitoring is an important task since it enables real-time tracking of animal health and behaviour, improving productivity, reducing losses, and ensuring better resource management in farming. This paper proposes a strategy to reduce the energy consumption of a microcontroller designed for livestock monitoring in a controlled environment using LoRaWAN and GPS technologies. The aim is to extend the monitoring period implementing a novel method based on the RSSI parameter. The strategy estimates the distance of the livestock to a gateway avoiding the need of continuously using a GPS. Experimental test for different periods of time were carried out, considering variable duty cycles depending on the position of the livestock with respect to the RSSI zone. An important reduction on the energy consumed by the microcontroller was obtained, validating the effectiveness of the proposed method.